Screening the Tortured Body The Cinema as Scaffold - de Valk, Mark.; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
Inspired by Michel Foucault's examination of state subjugation and control, this book considers post-structuralist notions of the 'political technology of the body' and 'the spectacle of the scaffold' as a means to analyse cinematic representations of politically-motivated persecution and bodily repression. Through a critique of sovereign power and its application of punishment 'for transgressions against the state', the collected works, herein, assess the polticised-body via a range of cinematic perspectives. Imagery, character construction and narrative devices are examined in their account of hegemonic-sanctioned torture and suppression as a means to a political outcome. Screening The Tortured Body: The Cinema as Scaffoldelicits philosophical and cultural accounts of the 'retrained' body to deliberate on a range of politicised films and filmmakers whose narratives and mise-en-scène techniques critique corporeal subjugation by authoritarian factions.
SECTION I - STATE EVISCERATION/TORTURED FLESH -- 1. Tortured Spectators: Massacred and Mucosal - Patricia MacCormack -- 2. Torture Porn: The American Sadistic Disposition in the Post 9/11 Horror Genre - Aaron Kerner -- 3. Discipline...But Punish!: Foucault, Agamben and Torture Porn's Thanatopolitical Scaffold - Xavier Aldana Reyes -- 4. The Expectational Body: The Becoming of the Tortured Vampire Horde in Daybreakers - Simon Bacon -- 5. An Apology for French Torturers: L'Ennemi intime - Nicole Beth Wallenbrock -- SECTION II - THE SUBJUGATED BODY-POLITIC AS SPECTACLE -- 6. The Ideological Purpose of Torture: Artur London's Nightmare of Reality in L'aveu/The Confession (Costa-Gavras, 1970) - Susan Hayward -- 7. Mr. Stone Goes To Washington: JFK 2.4 - Mark de Valk -- 8. Giorgio Agamben Meets the Wachowskis: The State of Exception in V for Vendetta (James McTeigue, 2006) - Melissa M. Jacques -- 9. Modes of Silence and Resistance: Chilean Documentary and Gender Torture - Lisa DiGiovani -- SECTION III - FRAMING SPECTATOR RECEPTION OF STATE RETRIBUTION -- 10. Torture Documentaries and Taxi To The Dark Side (Alex Gibney, 2007) - Julia Lesage -- 11. Zero Dark Thirty: A Filmmaker's Notion - Larra Anderson -- 12. Hypermediacy, Embodiment and Spectatorship in Brian De Palma's Redacted - Calvin Fagan -- 13. Enemy of the State: Framing the Political Assassin - Shane O'Sullivan -- 14. "She's a Killer": The Image of the Women of Zero Dark Thirty.Dorothea Olkowski.
Keywords: Motion pictures; Film Theory